(untitled) (Applied Biological Research, 2019)
The multidrug resistivity (MDR) of opportunistic microorganisms is still a major concern which requires the development of a new efficient drug with fewer side effects that can be added to the antifungal armamentarium. This study is the first to report the antifungal nature of proteins purified from the hemolymph of Zygogramma bicolorata, immunized with Micrococcus luteus (MTCC 106) and Escherichia coli (MTCC 443). Immunized hemolymph was assayed for antimicrobial sensitivity against pathCandida albicans (ITCC 4718) and Aspergillus niger (ITdiffusion method. The crude extract of hemolymph was separated and purified into fractions by low-pressure size exclusion chromatography using a Sephadex G-25 column. Protein estimation for crude fraction was performed by Lowry’s method followed by the assessment of antifungal activity. The study revealed that four fractions (fraction 6, 9, 11 and 15) out of 30 fractions exhibited activity against the test organisms and accommodated high and low molecular weight proteins/peptides of 120, 100, 90 and 66 kDa and two relatively low molecular weight polypeptides (36 and 18 kDa) respectively. Being MDR in dire matter, the efficacy of the drug is momentous.